Interactive Regulations of Dynamic Methylation and Transcriptional Responses to Recurring Environmental Stresses During Biological Invasions - Fu, Ruiying; Huang, Xuena; Chen, Yiyong; Chen, Zaohuang; Zhan, Aibin (Frontiers in Marine Science, 2021)
Deoxyribonucleic acid methylation and gene transcription have been proved as two underlying mechanisms involved in rapid plastic response to environmental stresses. However, it remains elusive on how DNA methylation regulates gene transcription under acute and recurring environmental challenges to form the stress memory, further contributing to invasion success during range expansions. Using a model invasive species Ciona robusta, we investigated the regulatory roles of DNA methylation on gene transcription and their contribution to the formation of stress memory at 30 genes under acute and recurring osmotic challenges simulated during the invasion process. We found the bimodal distribution of methylation level for the 68 mCpGs identified across all the genes after challenges, but only five sites were significantly correlated with the expression of their corresponding genes. These genes participated in the biological processes of Ca2+ transport and metabolism of lipid and proline. At the DNA methylation level, we found two early-responding and four tardy-responding sites of stress memory and these sites were functionally related to genes involved in the biosynthesis of proline, metabolism of lipid, and transport of taurine and Ca2+. At the transcriptional level, three tardy-responding and five early-responding memory genes were involved in the transport of ions, regulation of water channels, biosynthesis of taurine, and metabolism of lipid. Altogether, the findings here suggest that DNA methylation and gene transcription should work in concert to facilitate the formation of stress memory, thus further improving the performance of invaders under recurring environmental challenges during biological invasions.